PENYEBAB PERNIKAHAN DINI DAN DAMPAKNYA BAGI KALANGAN PEREMPUAN (STUDI KASUS DI KUA KECAMATAN BANJAREJO) KABUPATEN BLORA 2021 - Sa'adah, Latifatus (Jurnal Studi Islam dan Sosial, 2022)
The aim of this research is to determine the causes of early marriage and its impact on women in the KUA Banjarejo District in 2021. This research uses qualitative methods with a case study approach. The problem that will be analyzed in this research is what factors cause early marriage and its impact on women. Based on research conducted by the author, it shows that the factors causing early marriage in Banjarejo District, Blora Regency, are caused by several factors, including Matchmaking Factors, Educational Factors, Economic Factors, Social Factors and Pregnancy Out of Wedlock. Meanwhile, the impact of early marriage on women in Banjarejo District is Loss of Adolescence, Divorce, Domestic Violence and Family Disharmony.